AAV-KLF7 Promotes Descending Propriospinal Neuron Axonal Plasticity after Spinal Cord Injury - Wen-Yuan Li; Ying Wang; Feng-Guo Zhai; Ping Sun; Yong-Xia Cheng; Ling-Xiao Deng; Zhen-Yu Wang (Neural Plasticity)
DPSN axons mediate and maintain a variety of normal spinal functions. Unsurprisingly, DPSN tracts have been shown to mediate functional recovery following SCI. KLF7 could contribute to CST axon plasticity after spinal cord injury. In the present study, we assessed whether KLF7 could effectively promote DPSN axon regeneration and synapse formation following SCI. An AAV-KLF7 construct was used to overexpress KLF7. In vitro, KLF7 and target proteins were successfully elevated and axonal outgrowth was enhanced. In vivo, young adult C57BL/6 mice received a T10 contusion followed by an AAV-KLF7 injection at the T7–9 levels above the lesion. Five weeks later, overexpression of KLF7 was expressed in DPSN. KLF7 and KLF7 target genes (NGF, TrkA, GAP43, and P0) were detectably increased in the injured spinal cord. Myelin sparring at the lesion site, DPSN axonal regeneration and synapse formation, muscle weight, motor endplate morphology, and functional parameters were all additionally improved by KLF7 treatment. Our findings suggest that KLF7 promotes DPSN axonal plasticity and the formation of synapses with motor neurons at the caudal spinal cord, leading to improved functional recovery and further supporting the potential of AAV-KLF7 as a therapeutic agent for spinal cord injury.